PENDAMPINGAN MANAJEMEN EKSTRAKULIKULER BULUTANGKIS SMA NEGERI 3 SAMARINDA - Ilham Ilham; Syaiful Anwar (Universitas Pahlawan Tuanku Tambusai, 2022)
Extracurriculars are activities organized to meet the demands of mastery of study materials and lessons with time allocations that are arranged separately based on needs. Extracurriculars are one way to improve sports achievement, especially in this case, badminton. However, this will not happen if only students are trying to improve their achievement, extracurricular supervising teachers must also try to improve student achievement. This activity exists at every level of education from elementary school to university. Extracurricular activities are aimed at enabling students to develop their personalities, talents and abilities in various fields outside of the academic field. After carrying out team service, it is concluded that extracurricular management factors affect the achievement of each student. The results obtained are that the first extracurricular must have adequate facilities, the second is that it is no less important that the extracurricular must also have financial assistance to finance each activity and the third is proper scheduling starting from practice to matches. Keywords: management, badminton extracurricular